2008
DOI: 10.1097/jom.0b013e318180804f
|View full text |Cite
|
Sign up to set email alerts
|

Overview of Selected Infectious Disease Risks for the Corporate Traveler

Abstract: International business travel to under-developed and developing countries has increased considerably over the past two decades. Most of these destinations are endemic to a variety of infectious diseases, many of which are associated with considerable morbidity, mortality, or both and the nonimmune, unprepared corporate traveler is at risk. Comprehensive pretravel consultation is essential to prevent travel-related illness. This review addresses some of the infectious diseases that can be acquired during intern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Illness may disrupt business activities during or after travel, cause loss of time and productivity, and increase medical costs. 24 One study found higher rates of medical claims for almost all diseases categories after international travel by business travelers compared with their non-traveling colleagues; many claims were related to infectious diseases. 25 History has shown that diseases such as SARS, hepatitis A, measles, and tuberculosis have all been transmitted by individuals traveling for business and other occupational travelers 26 – 30 ; and infections such as these may be transmitted to non-traveling employees or the traveler's community.…”
Section: Discussionmentioning
confidence: 99%
“…Illness may disrupt business activities during or after travel, cause loss of time and productivity, and increase medical costs. 24 One study found higher rates of medical claims for almost all diseases categories after international travel by business travelers compared with their non-traveling colleagues; many claims were related to infectious diseases. 25 History has shown that diseases such as SARS, hepatitis A, measles, and tuberculosis have all been transmitted by individuals traveling for business and other occupational travelers 26 – 30 ; and infections such as these may be transmitted to non-traveling employees or the traveler's community.…”
Section: Discussionmentioning
confidence: 99%
“…Perhaps surprisingly, Bunn (2008) found that despite those significant risks identified by medical experts, many IBTs remain unaware of the risk of infection or do not follow recommendations provided. Common infectious diseases include: diarrhoea, influenza, yellow fever, typhoid fever, dengue fever, dengue haemorrhagic fever, malaria, hepatitis A and B, and human immunodeficiency virus (HIV) ( Hudson & Fortuna, 2008 ). The COVID-19 pandemic represents an especially stark reminder of such physical health issues.…”
Section: Current Debates In a Fragmented Field – A Value Perspectivementioning
confidence: 99%
“…9 Early trials demonstrated that mild reactions occur five to eight days after vaccination in 10-15% of vaccinees, with more severe reactions in only one to two per cent of cases. 10 Reactions vary from mild, comprising localised pain and erythema at the injection site, to headache, nausea, vomiting and diarrhoea. Systemic reactions are reported as occurring in fewer than 0.2% of cases, although they may be more common than thought.…”
Section: Tolerability and Safety Of Yellow Fever Vaccinesmentioning
confidence: 99%